2021
DOI: 10.1016/j.diabres.2021.108674
|View full text |Cite
|
Sign up to set email alerts
|

The DAR 2020 Global survey: Ramadan fasting during COVID 19 pandemic and the impact of older age on fasting among adults with Type 2 diabetes

Abstract: The DAR Global survey of Ramadan-fasting during the COVID-19 pandemic aimed to describe the characteristics and care in participants with type 2 diabetes (T2D) with a specific comparison between those <65 years and !65 years.Methods: Participants were consented to answer a physician-administered questionnaire following Ramadan 2020. Impact of COVID-19 on the decision of fasting, intentions to fast and duration of Ramadan and Shawal fasting, hypoglycaemia and hyperglycaemia events

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 13 publications
(42 reference statements)
2
28
2
5
Order By: Relevance
“…Ramadan fasting is a religious obligation for healthy Muslim adults [1]. Although the Quran exempts certain individuals from fasting [2], such as those who are ill, many Muslims with diabetes choose to participate in Ramadan fasting [3][4][5][6][7][8][9]. Studies confirmed that approximately 43%-80% of people with type 1 diabetes (T1D) [3,8,9] and 79%-95% of people with type 2 diabetes (T2D) fasted at least 15 days during Ramadan [3][4][5][6]; according to these studies, they fasted an average of 23-27 and 27 days, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Ramadan fasting is a religious obligation for healthy Muslim adults [1]. Although the Quran exempts certain individuals from fasting [2], such as those who are ill, many Muslims with diabetes choose to participate in Ramadan fasting [3][4][5][6][7][8][9]. Studies confirmed that approximately 43%-80% of people with type 1 diabetes (T1D) [3,8,9] and 79%-95% of people with type 2 diabetes (T2D) fasted at least 15 days during Ramadan [3][4][5][6]; according to these studies, they fasted an average of 23-27 and 27 days, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies during Ramadan in the Middle East, including those on patients with diabetes for instance ( 21 , 22 ) and our own experience in Emirati individuals with T1DM and T2DM in a prospective study has shown that at least 80% of these choose to fast most of Ramadan (unpublished data). Hence, extrapolating from Diabetes and Research alliance ( 16 ) surveys conducted in high-risk patients, it will be safe to assume that patients with thyroid disorders are even more likely to fast during Ramadan.…”
Section: Discussionmentioning
confidence: 94%
“…It is thus rational that those with a higher baseline fCal will be the most prone to clinical deterioration when an inciting factor (fasting) is present. Older patients are more prone to negative effects of fasting such as dehydration and hypoglycaemia, the symptoms of which might raise the “physician global assessment” part of the partial Mayo score [ 54 ]. Elderly patients also more commonly have comorbidities and have polypharmacy problems that are compounded during the month of Ramadan.…”
Section: Discussionmentioning
confidence: 99%